Oilseed crop production: Findings from the Myanmar Agriculture Performance Survey - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
Groundnut, sesame, soybean, and sunflower crops are grown across Myanmar. Nationally, 15 percent of farmers were engaged in oilseed cultivation in the post/pre-monsoon 2023 season, while 17 percent of farmers planted oilseeds in the 2022 monsoon season. Among the agro-ecological zones, the Dry Zone had the largest share of farmers growing oilseeds as their most important non-paddy crop. At the same time, the percentage of farmers who grew oilseeds as their most important non-paddy crop in 2023 declined overall and in the Dry Zone compared to the post/pre monsoon seasons of 2022 and 2021. In the post/pre-monsoon 2023 season, 7 and 6 percent of the farmers grew sesame and groundnut, respectively. Only 2 percent of farmers grew soybeans while 1 percent grew sunflowers. Groundnut, sunflower, and sesame were mainly grown in the Dry Zone, while soybean was mainly grown in the Hills and Mountainous Region. The farm size of oilseed growing households was slightly larger than that of the average crop growing household, 5.7 acres compared with 4.7 acres. Most oilseed farmers specialize in oilseed production and plant more than half of their cultivated acres to oilseeds. Oilseed farmers grew oilseeds on 64 percent of their cultivated acres in the 2023 pre/post monsoon season and 36 percent of their cultivated acres in the monsoon season.